Epistemología y construcción de una nueva disciplina científica: la didactique des mathématiques (ING) - Ruiz, Ángel; Chavarría, Jesennia; Alpízar, Marianella (Uniciencia, 2003)
A brief review about the French Didactique des Mathematiques is acomplished, and a theoretical assessment on these ideas is developed. We emphasize the epistemological aspect.